The constrained disorder principle: A novel framework for understanding glycemic variability and optimizing diabetes management - Orly Agmon; Tal Sigawi; Yaron Ilan (Endocrine and Metabolic Science)
Traditional diabetes management primarily focuses on controlling average glucose levels, typically assessed through HbA1c. However, emerging research highlights the significance of glucose fluctuations in influencing diabetes outcomes. Glycemic variability (GV) and glucose complexity are crucial yet often overlooked aspects of glucose regulation. This review introduces the Constrained Disorder Principle (CDP), a novel framework suggesting that biological systems function optimally within a controlled range of variability. Excessive and insufficient glucose fluctuations can be harmful, indicating a J-shaped relationship between GV and health outcomes. The CDP shifts the focus of diabetes management from simply minimizing GV to defining an optimal range that aligns with physiological glucose regulation. This approach enables more precise treatment targets. The CDP emphasizes the potential of variability-based treatment strategies, incorporating controlled fluctuations into therapy. These strategies aim to enhance adaptive responses, improve treatment efficacy, and reduce the development of resistance. By redefining the role of GV in diabetes care, the CDP may offer a transformative perspective that paves the way for more personalized, dynamic, and effective management strategies.